Implementasi Media Pembelajaran Educandy pada Materi Cerita Fantasi untuk Pembelajaran Kosakata di SMP - Olivia Septiana Setyo Wijayanti; Miftakhul Huda (Jayapangus Press, 2026)
This study aims to analyze the implementation of Educandy application-based learning media in vocabulary learning on students' fantasy story material. The research method used is a qualitative descriptive method. Data in the form of students' fantasy story works before and after the research implementation, questionnaires filled out by 25 students of class VIII A, and the results of interviews with Indonesian Language teachers at SMP Muhammadiyah 5 Surakarta. The data sources used in the study were students of class VIII A and teachers in charge of Indonesian Language subjects. Data collection techniques used were observation, questionnaires, interviews, and documentation. The collected data were then analyzed using the interactive analysis technique of the Miles and Huberman model, with the stages of data collection, data reduction, data presentation/verification and conclusions. This research was conducted in the odd semester of the 2025/2026 academic year at SMP Muhammadiyah 5 Surakarta which was chosen because it has adequate facilities that can integrate application-based learning media. The validity of the research data used technical triangulation. The implementation of Educandy media was carried out through three stages, namely the preparation stage, the learning implementation stage, and the closing or evaluation stage. The novelty in this research lies in the use of Educandy with a gamification approach for learning fantasy story vocabulary in junior high schools, which has implications for the research findings, namely increasing vocabulary variation, student participation, ease of understanding vocabulary through interactive games, and changes in the learning atmosphere to be more fun and collaborative.